The Impact of Social Media on Adolescent Personality in Psychosocial Perspective - Delvina Tri Agustin (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2021)
Advancement in technology has led to the emergence of social media applications that are widely adopted nowadays as a platform of communication. This brings a good impact on society, including on teenagers. From the perspective of social psychology, the use of social media affects teenagers’ personalities because social influence affects the decision-making process among teenagers. This article aims at revealing the use of social media among teenagers and its’ impact on their attitude towards the potential impacts of using social media. This article utilizes a survey result from a sample of teenagers from a junior high school is Samarinda. Findings show that teenagers use social media for entertainment and educational purposes. They are aware of the possibility that social media can be used as a platform to spread hoaxes and fake news due to the ability of the users to be anonymous during on social media.